Aquaculture Soft Coral Lobophytum crassum as a Producer of Anti-Proliferative Cembranoids - Peng, Bo-Rong (Mar Drugs, 2018)
Our continuous search for marine bioactive secondary metabolites led to the screening of crude extracts from a variety of aquaculture soft corals. The ethyl acetate (EtOAc) extract of Lobophytum crassum showed a distinctive chemical profile that was different from the wild type. It demonstrated significant anti-proliferative activity against Molt 4 leukemia cell with an IC(50) value of 1 μg/mL after 24 h. Chemical investigation focusing on the unique peaks in L. crassum profile led to the discovery of a new α-tocopherol crassumtocopherol C (1), and two new cembrane-based diterpenoids culobophylins D (2) and E (3), along with ten known cembranoids (4–13). The structures of these isolates were elucidated using extensive spectroscopic techniques and a comparison with previously published data of related metabolites. Compound 2 was found to possess the first identified saturated internal C(4)-O-C(14) linkage six-membered ring among all cembrane-type diterpenoids. The anti-proliferative activity of all the isolates (except 3) was evaluated against a limited panel of leukemia cell lines (Molt 4, K562, U937, and Sup-T1). The major compounds 8 and 10 exhibited the most anti-proliferative potent effect, with IC(50) values ranging from 1.2 to 7.1 μM. The Structure Activity Relationship (SAR) of the isolates suggested that the presence of lactone moieties is crucial for the anti-proliferative activity against leukemia cells. Our work indicated that the development of an efficient aquaculture protocols for soft corals led to the discovery of new secondary metabolites with unique structural features. Such protocols can lead to a sustainable supply of biologically active compounds in enough quantities for the pharmaceutical industry.